2021
DOI: 10.5217/ir.2020.00107
|View full text |Cite
|
Sign up to set email alerts
|

Very early onset inflammatory bowel disease in a South Asian country where inflammatory bowel disease is emerging: a distinct clinical phenotype from later onset disease

Abstract: cluding a severe and aggressive course of disease, predominant colonic involvement and a higher incidence of familial IBD compared to PIBD other than VEOIBD (6-17 years). 1 The incidence of PIBD is on the rise globally. 2 A complex interplay of genetic and changing environmental factors has been implicated for the rising incidence although specific factors are yet to be completely understood. 2-6 Most of the epidemiological data however are from the West including North America, Canada, and Europe. 3 A few rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…The prevalence of pediatric-onset IBD is increasing [25,26]. Pediatric cases have been reported to account for up to 25% of all IBD cases in Western countries.…”
Section: Age At Onsetmentioning
confidence: 99%
“…The prevalence of pediatric-onset IBD is increasing [25,26]. Pediatric cases have been reported to account for up to 25% of all IBD cases in Western countries.…”
Section: Age At Onsetmentioning
confidence: 99%
“…10,11 VEO-IBD, often defined as IBD diagnosed before 6 years of age, is associated with a different clinical phenotype, treatment response, and outcomes relative to children diagnosed at older ages. [12][13][14] Previous systematic reviews on the incidence and prevalence of pediatric-onset IBD have not explicitly described the epidemiology of VEO-IBD.…”
mentioning
confidence: 99%
“…More recent Indian studies, which included perianal disease developed both at diagnosis and subsequent follow-up, however, have found even lower rates than other Asian cohorts. Banerjee et al [ 40 ] reported 7.4% perianal involvement amongst CD patients and a multicentre paediatric study in India reported 10.9% of CD patients with perianal disease(fistula or abscess). These findings suggest South Asian CD patients in their native countries do not experience disproportionately high rates of perianal disease.…”
Section: Discussionmentioning
confidence: 99%